Clinical efficacy of nanosilver and chlorhexidine in the treatment of plaque-induced gingivitis: A randomized controlled clinical trial - Al-Sharani, Amani; Al-Hajj, Waddah; Madfa, Ahmed (University of Concepci?n in Chile, 2018)
Aim: The present study aimed to assess the clinical efficacy of nanosilver (NS) mouthwash and compared with chlorhexidine (CHX) mouthwash for the treatment of plaque-induced gingivitis. Materials and methods: Sixty-two (28 males and 34 females) plaque-induced gingivitis patients were allocated into two groups and asked to rinse with 10ml of NS or CHX, immediately after brushing, for 1 min, in the morning and evening. The plaque, gingival, and papilla bleeding indices were taken at baseline, two weeks, and finally at four weeks for each patient. The statistical analysis between and within groups were performed using Mann-Whitney U-test and Wilcoxon signed rank test respectively. Result: Intergroup comparison by Mann-Whitney U-test showed no statistically significant differences in the investigated groups at the baseline for all studied parameters. At 2 and 4 weeks follow up, the CHX group showed statistically significant lower plaque scores than the NS group (p<0.05). However, there is no statistically significant difference between NS and CHX groups for gingival and papilla bleeding scores (p>0.05). Both groups showed statistically significant reductions in plaque, gingival and papilla bleeding scores after 2 weeks and 4 weeks of product use when compared to baseline (p<0.001). Conclusion: Both mouthwashes decreased plaque, gingival and papilla bleeding scores, however the reduction in plaque scores was higher for the CHX group compared to the NS group.